Does emotional intelligence and empowering leadership affect psychological empowerment and work engagement?. Issue 8 (29th September 2020) - Alotaibi, Saad M.; Amin, Muslim; Winterton, Jonathan
Abstract : Purpose: The objective of this study is to investigate the role of emotional intelligence and empowering leadership in enhancing psychological empowerment and work engagement in private hospitals. Design/methodology/approach: A total of 500 questionnaires were distributed to staff nurses at five private hospitals in Riyadh, Saudi Arabia, 100 questionnaires to each hospital, with an achieved response rate of 34.8%. Findings: The results show statistically significant positive relationships between emotional intelligence, empowering leadership, psychological empowerment and work engagement. The relationship between emotional intelligence and work engagement and psychological empowerment and work engagement were not significant. Research limitations/implications: The study found that employees who have a high level of emotional intelligence and the positive stimulus of empowering leadership demonstrate enhanced psychological empowerment and work engagement. Practical implications: A better understanding of the role of EI and EL in enhancing psychological empowerment and work engagement could help hospitals reduce turnover among nurses and improve their relationships with patients, as well as maintaining competitive advantage. Originality/value: The study provides evidence to support the effect of EI on empowering leadership, psychological empowerment and work engagement in private hospitals.